CCL2-ethanol interactions and hippocampal synaptic protein expression in a transgenic mouse model - Gruol, Donna; Vo, Khanh; Bray, Jennifer; Roberts, Amanda (Frontiers in Integrative Neuroscience, 2014)
Chronic exposure to ethanol produces a number of detrimental effects on behavior. Neuroadaptive changes in brain structure or function underlie these behavioral effects and may be transient or persistent in nature. Central to the functional changes are alterations in the biology of neuronal and glial cells of the brain. Recent data show that ethanol induces glial cells of the brain to produce elevated levels of neuroimmune factors including CCL2, a key innate immune chemokine. Depending on the conditions of ethanol exposure, the upregulated levels of CCL2 can be transient or persistent and outlast the period of ethanol exposure. Importantly, results indicate that the upregulated levels of CCL2 may lead to CCL2-ethanol interactions that mediate or regulate the effects of ethanol on the brain. Glial cells are in close association with neurons and regulate many neuronal functions. Therefore, effects of ethanol on glial cells may underlie some of the effects of ethanol on neurons. To investigate this possibility, we are studying effects of chronic ethanol on hippocampal synaptic function in a transgenic mouse model that expresses elevated levels of CCL2 in the brain through enhanced glial expression, a situation know to occur in alcoholics. Both CCL2 and ethanol have been reported to alter synaptic function in the hippocampus. In the current study, we determined if interactions are evident between CCL2 and ethanol at the level of hippocampal synaptic proteins. Two ethanol exposure paradigms were used; the first involved ethanol exposure by drinking and the second involved ethanol exposure in a paradigm that combines drinking plus ethanol vapor. The first paradigm does not produce dependence on ethanol, whereas the second paradigm is commonly used to produce ethanol dependence. Results show modest effects of both ethanol exposure paradigms on the level of synaptic proteins in the hippocampus of CCL2 transgenic mice compared with their non-transgenic littermate controls, consistent with ethanol-CCL2 interactions. No evidence of toxic effects of CCL2 or CCL2-ethanol interactions was observed. Taken together, these results support the idea that ethanol induced astrocyte production of CCL2 can result in neuroadaptive changes that interact with the actions of ethanol.